Предмет: Алгебра,
автор: Настёна722002
упростить выражение: 10у-(12у-(у-6))
Ответы
Автор ответа:
0
10у-(12у-(у-6))=10у-(12у-у+6)=10у-12у+у-6=-у-6
Автор ответа:
0
10у-(12у-(у-6))=10у-(12у-у+6)=10у-(11у+6)=10-11у-6=-1у-6
ответ:
-1у-6
можно еще домножить на минус один,тогда получим: 1у+6
ответ:
-1у-6
можно еще домножить на минус один,тогда получим: 1у+6
Похожие вопросы
Предмет: Математика,
автор: Martynas22
Предмет: Информатика,
автор: Аноним
Предмет: Литература,
автор: sahloladavronova
Предмет: Математика,
автор: okvo19
Предмет: Биология,
автор: nikita09052001